Teacher Resilience in Facing Changes in Education Policy due to Covid-19 Pandemic - Muhammad Amin; Nuriadi Nuriadi; Henny Soepriyanti; Lalu Thohir (Institut Agama Islam Negeri Palopo, 2022)
This is a descriptive study aimed at investigating resilience among university teachers, especially in dealing with changes in education policies during the Covid-19 pandemic. The participants in this research were lecturers at the English education study programme at a state university in West Nusa Tenggara Province, Indonesia. The data were obtained through an online questionnaire which was distributed to all potential respondents. Among 39 teaching staff, 26 completed and returned the form. Based on the data analysis it was found that most of the teachers (86.6%) are classified as having high and very high resilience, with only 13.4% having moderate resilience, and none as low or very low resilience. Based on gender, the level of resilience for both male and female lecturers is within the same level of high resilience, with females having a slightly higher rate than males, at 63 and 59.5 respectively (within the range of 17-85). There is an interesting finding on how resilience relates to the length of tenure. Based on this final category, it was found that length of tenure negatively correlates with the level of resilience with tenure group of 1-6 years, 7-21 years and 21 years and above scoring 63.7, 61.7, and 56 respectively, although on average all groups are still categorised as having high resilience. The majority of these university professors also perceive the changing education policy as something inevitable. With regard to how they expect to be helped to better adapt to changes and maintain their resilience, for any new policies there should be clear planning of the policy, proof that they work well (not based on trial and error), early socialisation, adequate training and coaching, and evaluation of the effectiveness of policies being implemented.Keywords: Educational policies, pandemic, teacher resilience